2020
DOI: 10.1080/15384101.2020.1750811
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 mediates airway remodeling in asthma via activating FAK and MAPK signaling pathway

Abstract: YKL-40 is a chitinase-like protein which was significantly elevated in asthma patients and related closely to asthma severity and airway remodeling. Airway remodeling in asthma involves complicated physical and pathological processes, including increased airway smooth muscle mass due to proliferation, migration of airway smooth muscle cells, epithelial-mesenchymal transition (EMT) and sub-epithelial fibrosis. However, the precise effect and underlying mechanism of YKL-40 in this pathological alteration remaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The “antigen processing and presentation” and “two-component system” pathways associated with allergies were also upregulated at this stage. MAPK signaling was shown to be involved in airway inflammation and hyper-responsiveness in asthma ( Bao et al, 2017 ; Sun X. et al, 2020 ; Sun Y. et al, 2020 ). The members of the NOD-like receptor family promote inflammatory cell recruitment and regulate immune responses in different tissues, such as lung tissues ( Donovan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The “antigen processing and presentation” and “two-component system” pathways associated with allergies were also upregulated at this stage. MAPK signaling was shown to be involved in airway inflammation and hyper-responsiveness in asthma ( Bao et al, 2017 ; Sun X. et al, 2020 ; Sun Y. et al, 2020 ). The members of the NOD-like receptor family promote inflammatory cell recruitment and regulate immune responses in different tissues, such as lung tissues ( Donovan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chitinase 3-like 1 (CHI3L1), also known as breast regression protein 39 in mice and YKL-40 in humans, is known to bind IL-13Ra2. 29,133 The elevated levels of CHI3L1/YKL-40 are shown in the sera and skin lesions in AD patients. 133 CHI3L1/YKL-40 promotes fibrotic process 133 and further accelerates Th2 deviation.…”
Section: Il-13ra2 and Scratch Injurymentioning
confidence: 99%
“…29,133 The elevated levels of CHI3L1/YKL-40 are shown in the sera and skin lesions in AD patients. 133 CHI3L1/YKL-40 promotes fibrotic process 133 and further accelerates Th2 deviation. 134 These results suggest a possibility that the scratch-induced IL-13Ra2 upregulation may convert the keratinocyte response from IL-13-dominant to CHI3L1/YKL-40-dominant pattern.…”
Section: Il-13ra2 and Scratch Injurymentioning
confidence: 99%
“…YKL40 may promote the airway remodeling of asthma by activating FAK and MAPK signalling pathways, inducing epithelial mesenchymal transition (EMT) and subepithelial fibrosis. 93 Tang and colleagues 94 showed that serum YKL40 levels of Chinese patients with asthma were increased and correlated with the number of exacerbations. Serum YKL40 levels were correlated with total IgE, blood eosinophils and inversely with lung function and could predict the T A B L E 1 (Continued)…”
Section: Emerging Biomarkersmentioning
confidence: 99%